CH and CC bond insertion reactions of diazo compounds into aldehydes. Issue 49 (7th December 2017) - Guttenberger, Nikolaus; Breinbauer, Rolf
Abstract: This review covers formal insertion reactions of diazo compounds into aldehydes for the formation of ketones (CH bond insertion) and homologated aldehydes (CC bond insertion). The Roskamp homologation and related reactions have become powerful tools for the construction of CC bonds in organic synthesis. Recently, efficient catalytic asymmetric variants have been described for these formal insertion reactions, which have been enabled by chiral oxazaborolidinium catalysts. The power of diazoalkane–carbonyl homologation reactions is illustrated with applications in natural product syntheses. The review is complemented by a discussion of common side reactions and a presentation of in situ variants as safe alternatives for the production of diazo compounds, which omit the isolation of these hazardous reagents and will make applications even more attractive. Graphical abstract: